2014
DOI: 10.1128/jvi.03775-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanism of a Glycoside Compound Inhibiting Abnormal Prion Protein Formation in Prion-Infected Cells: Implications of Interferon and Phosphodiesterase 4D-Interacting Protein

Abstract: A new type of antiprion compound, Gly-9, was found to inhibit abnormal prion protein formation in prion-infected neuroblastoma cells, in a prion strain-independent manner, when the cells were treated for more than 1 day. It reduced the intracellular prion protein level and significantly modified mRNA expression levels of genes of two types: interferon-stimulated genes were downregulated after more than 2 days of treatment, and the phosphodiesterase 4D-interacting protein gene, a gene involved in microtubule gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Intracerebral or intraperitoneal infection was performed by inoculation with 20 or 100 μL, respectively, of a 1% (w/v) brain homogenate obtained from a terminally ill 263K prion-infected hamster. In case of continuous intracerebroventricular infusion, continuous infusion into the cerebral third ventricle was performed using an osmotic minipump and brain infusion kit, as previously described [49]. Mice were monitored every day until the time of terminal disease, at which time the mice were akinetic (with a lack of grooming behavior, coordination, and parachute reaction) or exhibited a rigid tail, an arched back, and weight loss of approximately 10% within one week.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intracerebral or intraperitoneal infection was performed by inoculation with 20 or 100 μL, respectively, of a 1% (w/v) brain homogenate obtained from a terminally ill 263K prion-infected hamster. In case of continuous intracerebroventricular infusion, continuous infusion into the cerebral third ventricle was performed using an osmotic minipump and brain infusion kit, as previously described [49]. Mice were monitored every day until the time of terminal disease, at which time the mice were akinetic (with a lack of grooming behavior, coordination, and parachute reaction) or exhibited a rigid tail, an arched back, and weight loss of approximately 10% within one week.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were monitored every day until the time of terminal disease, at which time the mice were akinetic (with a lack of grooming behavior, coordination, and parachute reaction) or exhibited a rigid tail, an arched back, and weight loss of approximately 10% within one week. The mice were killed at this stage and disease was confirmed by immunoblotting and immunohistochemical analyses of abnormal PrP deposition in the brain, as previously described [12,49]. Because it was difficult to determine the time of symptom onset in the animal model used in this study, survival time was defined as the time from prion infection to terminal disease.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these models, prion-infected cell models have been the most frequently used since Congo red and polyanionic glycans were found to possess antiprion activity (Caughey and Race 1992;Caughey and Raymond 1993). In fact, our research group has identified dozens of antiprion compounds, including quinacrine and compB, using prion-infected cell models (Doh-ura et al 2000(Doh-ura et al , 2007bIshikawa et al 2004Ishikawa et al , 2006Murakami-Kubo et al 2004;Kawatake et al 2006;Kawasaki et al 2007;Nguyen et al 2008Nguyen et al , 2011Hamanaka et al 2011Hamanaka et al , 2015Teruya and Doh-ura 2013;Nishizawa et al 2014). However, these cell models are not fully compatible with in vivo prion-infected neuronal cells.…”
Section: A Combination Of Multiple Targetsmentioning
confidence: 99%